Reinventing a territory? Snowboard establishment and development process in the Oisans area - Dorothée Fournier; Michaël Attali; Anne-Marie Granet Abisset (Revue de Géographie Alpine, 2019)
The transformations that Oisans has faced over the course of its history invalidates the idea that this mountain territory would live in self-sufficiency, without the inability to innovate. The situation of the 1980s considerably compromises the success of mountain tourism. Driven by the Californian counterculture, the innovation transmitted by snowboarding allows the Oisans to maintain its touristy character, while transforming the socio-cultural dimension of the territory. This article is based on a collection of data (municipal and intercommunal archives, interviews, regional daily press) to capture the development of representation systems of territorial operators. Focusing on the mechanisms of interrelations, this research wants to analyse the social process of innovation by breaking down the sequences that punctuate it, according to the operators, times and places, in order to characterize the repercussions on territoriality.